The Effect of Transactional Leadership Style, Entrepreneur’s Passion, and Organizational Commitment on Employee Performance with Job Satisfaction as an Intervening Variable on Employees - Godfrid, Ronald Junus; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to examine the influence of Transactional Leadership Style, Organizational Commitment, and Entrepreneurship Passion on Job Satisfaction and Employee Performance, as well as the mediating role of Job Satisfaction in the relationship. The results of statistical analysis show that Transactional Leadership Style has a significant positive influence on Job Satisfaction, with a very low significance value (p < 0.05). Likewise, Organizational Commitment and Entrepreneurship Passion are proven to significantly positively affect Job Satisfaction. In addition, Transactional Leadership Style, Organizational Commitment, and Entrepreneurship Passion also positively affect Employee Performance. Job Satisfaction is proven to be a significant mediator in the relationship between Transactional Leadership Style, Organizational Commitment, and Entrepreneurship Passion on Employee Performance. Overall, Job Satisfaction fully and significantly mediates the influence of the three variables on Employee Performance.